KARAKTERISTIK ADSORPSI ION LOGAM Cu(ll) PADA KITOSAN BEAD - , Sari Edi Cahyaningrum ([Yogyakarta] : Kelompok Studi Lingkungan Indonesia, 2007)
The characteristic adsorption of metal ion Cu(ll) on cbitosan and cbitosan bead was studied. Some parameters of adsorption were determined such as optimum of pH, the rate and capacity of adsorption. By Kyieldhal destruction, and than following with AAS analysis, it was founded that adsorption of metal ion Cu(II) on cbitosan and cbitosan bead have the same of optimum pH. The adsorption rate of metal ion Cu(ll) on cbitosan bead 'significant faster than on cbitosan. Modification with swelling process enhanced the adsorption capacity Cu(ll) on cbitosan.